The WTO law of subsidies : a comprehensive approach - Benitah, Marc. (b, 2019)
The WTO Law of Subsidies' provides a comprehensive analysis of the law of subsidies under the WTO regime. Subsidies are arguably the dominant theme in International Economic Law and a prolific case law has been elaborated by WTO Panels and Appellate Body in response to the multitude of complaints lodged in the past two decades (Softwood Lumber, Airbus, Boeing, etc.). The case law and norms disciplining subsidies under the WTO legal regime are of utmost importance first for international trade ministries, parliaments, and international institutions (OECD, CNUCED, FAO, etc.). However, non-governmental organizations (World Wide Fund, etc.) are also directly concerned by this topic regarding, for example, fisheries subsidies and their impact on overexploitation of marine resources. The private sector (fishing fleets, fishermen, extractive industries, etc.) is also affected by this topic particularly regarding future investments.
Part I. Scanning WTO agreements for cumulative disciplines and remedies to counter an alleged subsidy granted by another member (the perspective of the accusing member) -- Part II. Scanning WTO case law for strategies to refute violation of subsidies disciplines (the perspective of the accused subsidizing member) -- Part III. Scanning pending legal issues in the context of present norms.
Includes bibliographical references and index.
Keywords: World Trade Organization; Subsidies -- Law and legislation